Partisipasi Masyarakat Nelayan Dalam Pemberdayaan Ekonomi Di Desa Margasari, Kecamatan Labuhan Maringgai, Lampung Timur - Valentina, Annissa; Wardany, Kusuma; Mariana, Erni (Jurnal Masyarakat Maritim, 2020)
This study aims to determine the participation of fishermen in the implementation of economic empowerment activities in Margasari Village, Labuhan Maringgai District, East Lampung. This research is a field research. The research method used in this research is a qualitative approach. Data analysis uses qualitative analysis with data, conclusions using the method. Inductive. The results of this study indicate that the participation of fishermen in empowerment activities is very low because fishermen are not involved so that a strategy is needed that involves them not only on the implementation stage but also from planning to evaluation